Hole in my soul - Aerosmith; Svengali Merchandising; Sony Music Entertainment (New York : Svengali Merchandising, 1997)
Contains three versions of Aerosmith's song Hole In My Soul.
CD 1 : Hole In My Soul (Edit) / (4:32) -- AC Edit / (4:36) -- Album Version / (5:50).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English; Popular music